2019
DOI: 10.1016/j.ajhg.2019.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architectures of Childhood- and Adult-Onset Asthma Are Partly Distinct

Abstract: The extent to which genetic risk factors are shared between childhood-onset (COA) and adult-onset (AOA) asthma has not been estimated. On the basis of data from the UK Biobank study (n ¼ 447,628), we found that the variance in disease liability explained by common variants is higher for COA (onset at ages between 0 and 19 years; h 2 g ¼ 25.6%) than for AOA (onset at ages between 20 and 60 years; h 2 g ¼ 10.6%). The genetic correlation (r g ) between COA and AOA was 0.67. Variation in age of onset among COA-aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
251
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(272 citation statements)
references
References 90 publications
16
251
0
5
Order By: Relevance
“…Dupuytren's disease, which has a prevalence of more than 30% in some Northern European ethnicities, although it is lower in most of the world by 1-3 levels of magnitude, is an interesting example that was examined in this research. The alleles were randomly distributed throughout the model genome; these results are consistent with GWAS findings for asthma [53,98], schizophrenia [99], and other diseases [4].…”
Section: Allele Genetic Architecturesupporting
confidence: 82%
“…Dupuytren's disease, which has a prevalence of more than 30% in some Northern European ethnicities, although it is lower in most of the world by 1-3 levels of magnitude, is an interesting example that was examined in this research. The alleles were randomly distributed throughout the model genome; these results are consistent with GWAS findings for asthma [53,98], schizophrenia [99], and other diseases [4].…”
Section: Allele Genetic Architecturesupporting
confidence: 82%
“…The association between asthma and the 17q12-21 locus was first established in childhood asthma 6 and was then confirmed to be mainly driven by individuals with the early-onset form of the disease. 13,14 Using a familial cohort with a mean age of onset of seven and 22 years old for probands and other family members respectively can be considered a caveat for the study of this locus, principally since gene expression counts and DNA methylation levels are changing over time. However, the genetic association was replicated in a previous study performed with the SLSJ asthma cohort 11 and analyses using the imputed data in this study show similar results when taking account of all samples or only those with age of onset under 17 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Since the association between genetic variants and the disease occurring at the 17q12-21 locus is mainly driven by individuals with early-onset asthma, 13,14 correlation analyses were performed with DNA methylation levels from different mother-child duos for the two CpGs included in the significant mQTLs at GSDMA TSS. Analyses were between unaffected mother and affected child duos, all asthma status mother and affected child duos and affected mother and affected child duos to demonstrate the possible heritability of these DNA methylation levels.…”
Section: Locus In Naïve Cd4 + T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this notion, estimates for the heritability of asthma have ranged between 35% and 95% 3 , although those based on twin studies have been lower 4 . Genome-wide association studies (GWAS) have confirmed the contribution of genetic factors to risk of asthma, with over 140 susceptibility loci having been identified thus far [5][6][7][8][9][10][11][12][13] . However, the risk alleles, most of which are common in the population, still only explain a small fraction of the overall heritability for asthma [5][6][7] .…”
mentioning
confidence: 99%